Kebiasaan Makan Remaja Putri yang Berhubungan dengan Anemia : Kajian Positive Deviance - Alfishar Akib; Sri Sumarmi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Female adolescents are at risk of anemia due to the imbalance of nutrient intake and unhealthy consumption habits. Objectives: Research aimed to analyzed food consumption habits related to anemia of female college students. Moreover, this research aims to analyzed the positive deviance of female college students who did not experience anemia. Methods: A cross sectional study was conducted, with the sample of 60 were randomly selected from female college students aged 17-20 years old who live at female boarder of the Airlangga Universitas. The dependent varible was status of anemia, meanwhile independent variables were nutrient intake including the intake of carbohydrate, protein, vitamin C and Fe, enhancer and inhibitor subtances. Pearson correlation test was used for ratio data, while Spearman correlation test was used for nominal and category data. In-depth interview was used to explore the positive habits of respondents who did not suffer from anemia. Results: The result shows that 70% of the respondents was anemia. The Most poor nutrition intake among respondents was intake of vitamin C and Fe (95%). Moreover, there is a correlation between the intake of protein (p=0.027) and enhancer substance (p=0.046) with the anemia status. However, the intake of carbohydrate (p=0.275), vitamin C (p=0.132) and Fe (p=0.618) and inhibitor substance (p=0.771) did not show any correlation with status of anemia status. The informants stated that their positive consumption habits are consuming animal protein and fruits rich of vitamin C, cooking by her self and choosing healty snacks.Conclusion : The intake of protein and enhancer substances has related with the anemia status of the female adolescents. This is partly due to consumption habits of sufficient animal proteins and fruits rich of vitamin C.ABSTRAK Latar Belakang: Remaja putri berisiko mengalami anemia, disebabkan oleh asupan gizi yang rendah dipicu oleh kebiasaan makan remaja yang tidak sehat. Diantara remaja mungkin ada yang tidak anemia, meskipun berada di lingkungan yang kurang mendukung.Tujuan: Penelitian bertujuan untuk menganalisis asupan zat gizi dan kebiasaan makan yang berhubungan dengan status anemia, serta mengkaji kebiasaan makan positif pada remaja yang tidak anemia.Metode : Penelitian dengan rancangan cross sectional, dilakukan di asrama putri Universitas Airlangga. Besar sampel 60 mahasiswi berusia 17-20 tahun diambil dengan metode simple random sampling. Variabel yang tergantung adalah status anemia dan variabel bebas adalah asupan zat gizi meliputi karbohidrat, protein, vitamin C dan mineral Fe serta asupan zat enhancer dan inhibitor bagi penyerapan zat besi. Uji korelasi Pearson digunakan untuk data berskala rasio dan korelasi spearman untuk data nominal dan kategori. In-dept interview, dilakukan untuk menggali kebiasaan makan responden yang tidak anemia.Hasil: Sebesar 70% responden mengalami anemia. Sebagian besar (95%) responden asupan vitamin C dan Fe tergolong kurang. Ada hubungan antara asupan protein (p=0,027) dan zat enhancer (p=0,046) dengan status anemia. Tidak ada hubungan antara asupan karbohidrat (p=0,275), vitamin C (p=0,132) dan Fe (p=0,618) serta asupan zat inhibitor (p=0,771) dengan status anemia. Kebiasaan makan positif pada remaja putri yang tidak anemia adalah sering mengkonsumsi protein hewani, memilih buah sumber vitamin C, memasak diwaktu luang dan memilih snack bergizi.Kesimpulan: Asupan protein dan zat enhancer berhubungan dengan status anemia pada remaja putri. Hal ini disebabkan kebiasaan mengkonsumsi protein hewani dan buah-buahan dengan kandungan vitamin C tinggi.